Orbit - Block, Thomas H. (New York : Coward, McCann & Geoghegan, 1982)
Star Streak Hypersonic airliner, which is the successor to the supersonic Concorde. During a routine flight, an unexplainable engine malfunction hurls Consolidated Flight 14 far too high and into a low-earth orbit. With only limited oxygen onboard, Captain Donald Collins is about to try a desperate and unproven maneuver to save the ship and its 100 passengers. On the ground, one of the designers of the aircraft has discovered evidence that the airliner might have been sabotaged. It becomes a race against time and the inescapable laws of physics to save the airliner and those onboard who are still alive.
National College of Business and Arts
Keywords: Hypersonic planes -- Fiction; Action and adventure fiction